Relationship between anemia and its correlates and cognitive function in Chinese patients with chronic schizophrenia: A large cross-sectional study - Yang Jiang; Yi Cai; Yaoyao Lu; Guanghui Wu; Xiang-Yang Zhang (Schizophrenia Research: Cognition, 2024)
Background: Although both anemia and schizophrenia (SCZ) can cause cognitive decline, it is unclear whether anemia worsens cognitive decline in patients with SCZ. The primary objective of this study was to investigate the prevalence of anemia and the relationship between anemia, SCZ symptom severity, and cognitive function in patients with SCZ. Methods: We obtained demographic and clinical data from 1690 inpatients with SCZ. All psychiatric symptoms and cognitive functioning were assessed by the Positive and Negative Syndrome Scale (PANSS), the Mini-Mental State Examination (MMSE), and the Repeated Battery for the Assessment of Neuropsychological Status (RBANS). Hemoglobin (HGB) values as well as red blood cell (RBC) counts were collected by routine blood tests. Results: The proportion of anemia in patients with SCZ was 26.36 % (383/1453). Compared to SCZ patients without anemia, SCZ patients with anemia were older, had a lower bodyweight, a smaller waist circumference and lower apolipoprotein B levels, but longer QT intervals. Further logistic regression analysis revealed that anemia was associated with age, gender, and weight. In addition, there was no difference in cognitive function between SCZ patients with and without anemia. Conclusion: Our findings suggest a high proportion of anemia in patients with chronic SCZ in the Han Chinese population. Several demographic and clinical variables are associated with anemia in SCZ patients.